(untitled) - Vollmann, Thomas E. (Boston, Mass., 1996)
Argues that change initiatives, such as reengineering, continuous improvement, and employee empowerment, can only succeed when they are implemented throughout the organization, and shares case studies
Keywords: Thay đổi tổ chức,Organizational change; Quản lý,Management